The Link Between Klebsiella and Ankylosing Spondylitis in Worldwide Geographical Locations - Rashid, Taha; Ebringer, Alan; Wilson, Clyde (Current Rheumatology Reviews, 2016)
Ankylosing spondylitis (AS) is a world-wide chronic inflammatory disease of the axial skeleton most likely caused by a microbial factor in genetically susceptible individuals. Over the last 40 years extensive data has been produced which shows that the majority of patients with AS possess the HLA-B27 genetic marker. Significantly elevated levels of Klebsiella antibodies have been demonstrated in 1556 AS patients in 16 different countries with various geographical locations. Other evidence for the link between Klebsiella and AS include increased fecal isolation rates of Klebsiella microbes in AS patients together with shared molecular and immunological cross-reactivity features existing between Klebsiella antigens and HLA-B27 and collagens I, III and IV. Anti-Klebsiella measures could possibly be included with the currently used medical treatment in the management of patients with AS.
Keywords: Geographical locations